Strategic Interactions between an Independent Central Bank and a Myopic Government with Government Debt - Stehn, Sven Jari (IMF Working Papers; Working Paper, 2008)
We analyse optimal discretionary games between a benevolent central bank and a myopic government in a New Keynesian model. First, when lump-sum taxes are available and public debt is absent, we show that a Nash game results in too much government spending and excessively high interest rates, while fiscal leadership reinstates the cooperative outcome under discretion. Second, we show that this familiar result breaks down when lump-sum taxes are unavailable. With government debt, the Nash equilibrium still entails too much public spending but leads to lower interest rates than the cooperative policy, because debt has to be adjusted back to its pre-shock level to ensure time consistency. A setup of fiscal leadership does not avoid this socially costly outcome. Imposing a debt penalty onto the myopic government under either Nash or fiscal leadership raises welfare substantially, while appointing a conservative central bank is less effective.